2018
DOI: 10.1161/hypertensionaha.118.11343
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal MicroRNA Profile Determines Endothelial Function in Offspring of Hypertensive Pregnancies

Abstract: Offspring of hypertensive pregnancies are at increased risk of developing hypertension in adulthood. In the neonatal period they display endothelial cell dysfunction and altered microvascular development. MicroRNAs, as important endothelial cellular regulators, may play a role in this early endothelial dysfunction. Therefore we identified differential microRNA patterns in endothelial cells from offspring of hypertensive pregnancies and determined their role in postnatal vascular cell function. Studies were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
(53 reference statements)
2
26
0
Order By: Relevance
“…While the precise mechanisms are yet to be fully elucidated, potential mediators for the abnormalities in vascular development in the offspring of preeclamptic pregnancies include derangement of maternal angiogenic factors, inherited polymorphisms, epigenetic factors, and altered microRNA expression [154,159,160]. Yu et al [159] analysed the maternal angiogenic profile alongside assessments of neonatal endothelial cells at birth, and vascular density in the offspring at three months postpartum in hypertensive and normotensive pregnancies.…”
Section: Long-term Impact On the Offspringmentioning
confidence: 99%
See 1 more Smart Citation
“…While the precise mechanisms are yet to be fully elucidated, potential mediators for the abnormalities in vascular development in the offspring of preeclamptic pregnancies include derangement of maternal angiogenic factors, inherited polymorphisms, epigenetic factors, and altered microRNA expression [154,159,160]. Yu et al [159] analysed the maternal angiogenic profile alongside assessments of neonatal endothelial cells at birth, and vascular density in the offspring at three months postpartum in hypertensive and normotensive pregnancies.…”
Section: Long-term Impact On the Offspringmentioning
confidence: 99%
“…This disruption of microvascular development was proportional to peripartum levels of maternal sFlt-1, implicating a role for maternal angiogenic factors in the abnormal development of the foetal vasculature in hypertensive pregnancies [159]. The neonatal microRNA profile also appears to play a role in mediating endothelial changes in the offspring of hypertensive pregnancies [160]. In particular, a specific microRNA involved in endothelial gene regulation, miR-146a, was shown to differ significantly between offspring of normotensive and hypertensive pregnancies, with direct correlations to HUVEC proliferation capacity and tube formation.…”
Section: Long-term Impact On the Offspringmentioning
confidence: 99%
“…Exposure to a hypoxic intrauterine environment is associated with offspring vascular, metabolic, and cardiac modifications including aortic wall thickening, loss of NO vessel modulation, altered LV function, and increased susceptibility to ischemia and metabolic syndrome [110][111][112]. Recently, it has become apparent that offspring of hypertensive pregnancies may also have microvascular genotypic and phenotypic abnormalities that may persist beyond the perinatal period and into adulthood [113][114][115][116], which may account for their significantly lower threshold for the development of cardiovascular-related diseases [110]. While studies assessing the specific impact of preeclampsia on cardiac remodeling during the transition from fetal to neonatal life remain limited, further investigations are needed given that adolescents and young adults who were exposed to maternal preeclampsia display unique LV remodeling patterns including greater relative wall thickness, smaller internal cavity diameter, and lower longitudinal peak systolic strain [112,117].…”
Section: Impact Of Pregnancy Complications On Early Cardiac Remodelingmentioning
confidence: 99%
“…The study of the role that miRs may have in the different cell types present in the placenta is indispensable to understand the role of this molecules in the development of the disease. In the long term, it has also been shown that miRNA profiles in the neonate is altered following an hypertensive pregnancy; for instance the level of mir-146a at birth predict microvascular development three months later [262].…”
Section: Epigenetic Alterations In Preeclampsiamentioning
confidence: 99%